2022
DOI: 10.1186/s12893-022-01641-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of a new skin antiseptic olanexidine gluconate in gastrointestinal cancer surgery

Abstract: Background Surgical site infection (SSI) is a common complication of gastrointestinal surgery. Olanexidine gluconate (OLG) is a novel skin antiseptic that is effective against a wide range of bacteria. The purpose of this study was to evaluate the bactericidal efficacy of OLG in gastrointestinal cancer surgery. Methods This retrospective study included a total of 281 patients who underwent gastrointestinal cancer surgery (stomach or colon). The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…7 In contrast, Kubo et al could not demonstrate an additional effect of the laparoscopic approach in the 1.5% olanexidine group (effect size 0.636, 95% confidence interval: 0.138-2.930, p = 0.562). 11 Our study also could not demonstrate the advantage of laparoscopic surgery (12.3% vs. 11.6%, adjusted risk ratio: 1.054, 95% confidence interval: 0.652-1.704); however, some reasons can explain this result: (1) We enrolled patients undergoing surgical procedures with intestinal resection. (2) We enrolled patients with operative wound class III and IV surgeries.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…7 In contrast, Kubo et al could not demonstrate an additional effect of the laparoscopic approach in the 1.5% olanexidine group (effect size 0.636, 95% confidence interval: 0.138-2.930, p = 0.562). 11 Our study also could not demonstrate the advantage of laparoscopic surgery (12.3% vs. 11.6%, adjusted risk ratio: 1.054, 95% confidence interval: 0.652-1.704); however, some reasons can explain this result: (1) We enrolled patients undergoing surgical procedures with intestinal resection. (2) We enrolled patients with operative wound class III and IV surgeries.…”
Section: Discussionmentioning
confidence: 57%
“…Obara et al reported that the laparoscopic approach significantly decreased SSI incidence in the 1.5% olanexidine group (4% vs. 12%, adjusted risk ratio: 0.35, 95% confidence interval: 0.17–0.74) 7 . In contrast, Kubo et al could not demonstrate an additional effect of the laparoscopic approach in the 1.5% olanexidine group (effect size 0.636, 95% confidence interval: 0.138–2.930, p = 0.562) 11 . Our study also could not demonstrate the advantage of laparoscopic surgery (12.3% vs. 11.6%, adjusted risk ratio: 1.054, 95% confidence interval: 0.652–1.704); however, some reasons can explain this result: (1) We enrolled patients undergoing surgical procedures with intestinal resection.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations